Biological Soil Crusts of Arctic Svalbard—Water Availability as Potential Controlling Factor for Microalgal Biodiversity - Borchhardt, Nadine; Baum, Christel; Mikhailyuk, Tatiana; Karsten, Ulf (Frontiers in Microbiology, 2017)
In the present study the biodiversity of biological soil crusts (BSCs) formed by phototrophic organisms were investigated on Arctic Svalbard (Norway). These communities exert several important ecological functions and constitute a significant part of vegetation at high latitudes. Non-diatom eukaryotic microalgal species of BSCs from 20 sampling stations around Ny-Ålesund and Longyearbyen were identified by morphology using light microscopy, and the results revealed a high species richness with 102 species in total. 67 taxa belonged to Chlorophyta (31 Chlorophyceae and 36 Trebouxiophyceae), 13 species were Streptophyta (11 Klebsormidiophyceae and two Zygnematophyceae) and 22 species were Ochrophyta (two Eustigmatophyceae and 20 Xanthophyceae). Surprisingly, Klebsormidium strains belonging to clade G (Streptophyta), which were so far described from Southern Africa, could be determined at 5 sampling stations. Furthermore, comparative analyses of Arctic and Antarctic BSCs were undertaken to outline differences in species composition. In addition, a pedological analysis of BSC samples included C, N, S, TP (total phosphorus) and pH measurements to investigate the influence of soil properties on species composition. No significant correlation with these chemical soil parameters was confirmed but the results indicated that pH might affect the BSCs. In addition, a statistically significant influence of precipitation on species composition was determined. Consequently, water availability was identified as one key driver for BSC biodiversity in Arctic regions.